Mechanisms of cognitive control in cadet pilots. Issue 1 (December 2016) - Gordon, Shirley; Getter, Nir; Oz, Idit; Garbi, Dror; Todder, Doron
Abstract Background Optimizing performance of aviators while minimizing risks arising from the exposure to extreme environment, both external and internal, is one of the principles guiding the Israeli Air Force. Young cadets in particular are considered an "at risk" population due to the fact that they have no experience in flight in the first stages of training and are therefore subjects for investigation. Methods In this study, we investigated the cognitive performance of young cadet pilots across different hours of the day. 39 cadets were randomly divided into 3 groups: morning, late afternoon, and late evening groups and then tested on a cognitive battery that contained both simple performance measures but also complex measures like dual-tasking and mental rotation test. Results The analysis indicated a significant effect of 'time of day' on the participants' accuracy [F (2, 32) = 3.4, p < 0.05]. In a post hoc pairwise t-tests, we found a near significant (p = 0.52) increase in participants' accuracy and a significant increase [F (2, 32) = 4.5, p < 0.05] in participants' reaction time in the late evening group as compared to the morning group. We also found a differential effect of dual tasking on accuracy in the different daytimes [F (2, 33) = 5.6, p < 0.01]. In a post hoc analysis, we found that accuracy in the 1-back task deteriorates from single task condition to the dual task condition only in the morning group (p < 0.05), but not in the late evening or late-afternoon group. Conclusions This 'trade-off' behavior, slowing down in order to perform better, in the late evening group may be a result of a voluntary control mechanism (top-down processes) activated at night, in this group. The combination of feeling fatigue, along with the understanding that complex tasks are more resource consuming, caused the cadets to check and double-check before answering, whereas in the morning group, they felt alert and vital, and acted more reactively, ended in an impulsive manner that caused to inaccurate performance.